(untitled) (Bangladesh Veterinarian, 2016)
A retrospective cohort study was conducted from July 2012 to August 2013 to determine prevalence of ovine footrot in chars (Shoals) of Mymensingh Sadar Upazila, Bangladesh, centred in Paranganj Union Parishad. A field survey used a prepared questionnaire and investigation of farm management. The prevalence of ovine footrot was 4.2% in the study group of 687 sheep, in 106 farms. The prevalence differed according to farm type and housing system. Prevalence of ovine footrot was higher (9.5%) in farms where sheep and other livestock were housed under the same roof. Prophylactic medication and footbath practice were absent. Common care and management practices were sheep bath, house and floor cleaning, deworming, and therapeutic medication. Highest prevalence (7.0%) was recorded in farms where prophylactic medication and deworming was irregular, and antiseptics were not used in sheep bathing and cleaning of sheep house and floor. The results suggest that improvement of the housing environment and management practices are required to control footrot. Bangl. vet. 2014. Vol. 31, No. 2, 74-83